1.rozwiąż równania
a)(4-2x)-(x+3)=(x-5)+(-3-x)
b)(3-2x)+(3x+3)=-(3-2x)+(5x+4)
c)-(x+3)+(2x-1)=(1+4x)+(3+x)
d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)

2.rozwiąż równania
a)(3-2x)-(x+4)-(2x-5)=(3x-4)-(5x+7)
b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)

3

Odpowiedzi

2010-03-28T14:22:03+02:00
1.rozwiąż równania
a)(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-3x+1 = -8
-3x = -8-1
-3x=-9 |:(-3)
x=3
b)(3-2x)+(3x+3)=-(3-2x)+(5x+4)
3-2x+3x+3 = -3+2x+5x+4
x+6=7x+1
x-7x=1-6
-6x=-5 |:(-6)
x=⅚
c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
x-4=5x+4
x-5x=4+4
-4x=8 |:(-4)
x= -2
d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x-11=-2
-3x=-2+11
-3x=9 |:(-3)
x=-3

2.rozwiąż równania
a)(3-2x)-(x+4)-(2x-5)=(3x-4)-(5x+7)
3-2x-x-4-2x+5=3x-4-5x-7
-5x+4=-2x-11
-5x+2x=-11-4
-3x=-15 |:(-3)
x=5
b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
-2x-3=-3x-4
-2x+3x=-4+3
x=-1
c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
3x+1=-4x+10
3x+4x=10-1
7x=9 |:7
x=⁹/₇
x=1²/₇
d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
-8=8x-13
8x=-8+13
8x=5 |:8
x=⅝
2010-03-28T14:30:37+02:00
1.rozwiąż równania
a)(4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-3x+1 = -8
-3x = -8-1
-3x=-9 |:(-3)
x =3
b)(3-2x)+(3x+3)=-(3-2x)+(5x+4)
3-2x+3x+3 = -3+2x+5x+4
x+6=7x+1
x-7x=1-6
-6x=-5 |:(-6)
x = 5/6
c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
x-4=5x+4
x-5x=4+4
-4x=8 |:(-4)
x = -2
d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x-11=-2
-3x=-2+11
-3x=9 |:(-3)
x =-3

2.rozwiąż równania
a)(3-2x)-(x+4)-(2x-5)=(3x-4)-(5x+7)
3-2x-x-4-2x+5=3x-4-5x-7
-5x+4=-2x-11
-5x+2x=-11-4
-3x=-15 |:(-3)
x =5
b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
-2x-3=-3x-4
-2x+3x=-4+3
x =-1
c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
3x+1=-4x+10
3x+4x=10-1
7x=9 |:7
x =9/7
x =1 2/7
d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
-8=8x-13
8x=-8+13
8x=5 |:8
x = 5/8
2010-03-28T14:34:04+02:00
A)(4-2x)-(x+3)=(x-5)+(-3-x) a)(3-2x)-(x+4)-(2x-5)=(3x-4)-(5x+7)
4-2x-x-3=x-5-3-x 3-2x-x-4-2x+5=3x-4-5x-7
1-3x=-8 4-5x=-2x-11
-3x=-9 -3x=-15
x=3 x=5
b)(3-2x)+(3x+3)=-(3-2x)+(5x+4) b)(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
3-2x+3x+3=-3+2x+5x+4 4-x-2x-3+x-4=-2x+3-x-7
6-x=1+7x -3-4x=-3x-4
5=8x 1=x
x=5/8 x=1
c)-(x+3)+(2x-1)=(1+4x)+(3+x) c)(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
-x-3+2x-1=1+4x+3+x 4x-5+ x-7-2x+8= -3x+4-x+6
x-4=4+5x 3x-4=-4x+10
-8=4x 7x=14
x=-2 x=2
d)-(x+3)-(2x+8)=(-3-2x)+(2x+1) d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-x-3-2x-8=-3-2x+2x+1 -4+2x-2x-4=3x-1+2x-5-7+3x
-3x-11=-2 -8=8x-13
-3x=9 5=8x
x=-3 x=5/8